Efforts to Eradicate Corruption through the Concept of Structural Legal Aid - Hidayat, Hidayat (Universitas Muhammadiyah Yogyakarta, 2024)
Corruption is a serious problem in the life of society and the progress of a nation. The impact is detrimental to the community, starting with not being able to enjoy development facilities, hampering economic growth, and so on. Therefore, seeing that this corruption problem has become a deadly virus, a precise concept is needed to solve it. That is through the concept of structural legal aid. The concept calls for community participation to eradicate corruption. In other words, people who are direct victims of corruption can advocate for corruption issues and cases. This concept aims to pick up, grab, and restore the rights of people who have been corrupted. So then, based on this corruption problem, an idea is offered to solve it. This research uses juridical-empirical research with a statute approach, a case approach, and a conceptual approach. Furthermore, to strengthen the ideas in this study, we interviewed people from the LBH-YLBHI Institute, SAHdaR Sumut, and other sources. In addition, this research will be supported by secondary data based on legal literature, documents, and others related to the theme of this research. The result of this research is that structural legal aid is able to eradicate corruption, which makes the community the main actor in eradicating criminal acts of corruption through education, prevention, and prosecution.